Digitalization in Political Relations: Planes for Perception and Mechanisms for Transformation - A. E. Konkov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The process of digital technologies development and their comprehensive integration into people’s lives influences consecutively different social processes. Mostly such an influences relieves at the present moment in the economic sphere, where digital economy gets to be one of the key priorities all over the world. Also processes of digitalization are likely to touch education, health care, law, they filter through political relations too. The article dwells upon analyzing directions for such an infiltration and mechanisms for transforming political sphere of society because of their pressure, generalizes digital practices in the political discourse. The author attempts in particular to evaluate retrospectively prerequisites and initial characteristics for involving web instruments by political actors, to define specific features of digital environment as a new domain for social and political relations, to capture process and functional characteristics for applying consecutive technologies. The specific emphasize is made on Russian experience of regulating and applying the political dimension of digital technologies, which reveals the active search by government for some national vision of digital policy both inside and outside as far as state borders are not likely to apply to the web space. Based on approaching consecutive practices the author distinguishes three meaningful planes (directions) to consider digitalization in political relations: digital democracy, which characterizes upscaling deliberative mechanisms for public policy with web communication opportunities; digital bureaucracy, which reflects advanced skills of political establishment and emerging technocratic platforms based on advanced e-government: and also digital diplomacy, which makes it possible for involving new technologies into politi cal achievements on the international and supranational arena.